Just right for the night - Ray, Stephen (Nelson London, 1994)
"Just Right for the Night" is a soothing bedtime story that follows a young child as they prepare for sleep. The narrative explores the comforting routines and rituals that help ease the transition to bedtime, such as snuggling with a favorite blanket, reading a story, and saying goodnight to loved ones. With gentle rhymes and calming illustrations, the book creates a cozy atmosphere, promoting relaxation and a sense of security, making it perfect for winding down at the end of the day.